The impact of e-WOM, e-advertisement and trendiness of food and beverage on tiktok towards purchase intention in Klang Valley - Ahmad Nazri, Nur Zafira Nabila; Rostam Affandi, Fatin Nurhafizah; Amirruddin, Muhamad Amirul Badlishah; Azli, Azwan Faris; Mohammad, Tajulurrus (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2025)
This study investigates the impact of electronic word-of-mouth (e-WOM), digital advertising, and trendiness on TikTok in shaping purchase intentions in the food and beverage sector within the Klang Valley. A quantitative survey was conducted with 396 respondents, and the data were analyzed using correlation and regression techniques. The results reveal that all three factors significantly affect purchase intention, with digital advertising being the strongest predictor, followed by trendiness and e-WOM. These findings suggest that while advertising effectiveness is maximized through visually engaging content, trend responsiveness and peer-driven narratives also play important supporting roles in driving consumer behaviour. This study contributes by clarifying the relative strength of these three drivers in a short-form video context, offering practical guidance for food and beverage marketers and advancing theoretical understanding of how social media platforms such as TikTok shape consumer decision-making.